EXPERIENTIAL MARKETING SEBAGAI SUATU STRATEGI DALAM MENCIPTAKAN CUSTOMER SATISFACTION DAN REPEAT BUYING UNTUK MENINGKATKAN KINERJA PEMASARAN - Farida Indriani (JURNAL STUDI MANAJEMEN ORGANISASI, 2012)
ABSTRACT Experiential marketing represent the alternative from excellence competition had by company as asset able to improve the marketing performance. Experiential marketing had by company can assist the company to peep out the new idea in each planning compilation, peculiarly in compiling marketing strategy.  That way also by improving experiential marketing strategy continously, company quickly can anticipate the change that happened around company through the strategy which application. And with the mecanism expected by a company can create customer satisfaction and repeat buying to improve the market performance.   Keywords : experiental marketing;  customer satisfaction;  repeat buying; market performance